Earnings Management and Audit Quality in China - ZHENG, JING (2017)
This paper examines the relationship between audit quality and earnings management in China, including both accruals earnings management and real earnings management. This paper is based on the assumption that if firms’ ability to manipulate accounting flexibility is restricted by higher audit quality, firms may resort to manipulations via real activities. Big N auditor and state-level auditor industry expertise are used as proxies for audit quality. The results show that Big N auditors are associated with lower abnormal accruals while higher levels of real earnings management. Similar, albeit weaker, results are found for state-level auditor industry expertise. Keywords: accruals earnings management; real earnings management; audit quality; Big N; industry expertise; China.